Optimizing the amount of pig manure in the vermicomposting of spent mushroom (Lentinula) substrate - Shi, Yajing; Wang, Zhenyu; Wang, Yurong (PeerJ, 2020)
Background The mushroom industry produces a large amount of spent mushroom substrate (SMS), which requires a large geographical footprint and causes pollution. Methods We sought to optimize the C:N ratio of the initial feedstock used in vermicomposting of SMS by adding pig manure additions. We applied five treatments to the initial feedstock (S0, S1, S2, S3, and S4) with different C:N ratio of approximately 35, 30, 25, 20, and 15, respectively. Results Our results showed that lignin and cellulose in SMS were degraded after 56 days vermicomposting, especially in S2 (77.05% and 45.29%, respectively) and S3 (65.05% and 48.37%, respectively) treatments. We observed the degradation of the fibrous structure in SMS using pig manure treatments after vermicomposting by microscope and scanning electron microscope. Cellulase and polyphenol oxidase (PPO) were enhanced in pig manure treatments during vermicomposting, especially in the S2 and S3 treatments. The biomass of earthworms in the S2 treatments was at its highest level among all treatments at 28 to 56 days. The high level of PPO activity in the S2 treatment may protect cellulase and earthworms against the aromatic toxicity that is a byproduct of lignin degradation, particularly at 28 to 56 days of vermicomposting. Conclusively, it indicated that the C/N ratio of 25 in the S2 treatment was the optimal for SMS vermicomposting with the addition of pig manure. Our results provide a positive application for the recycling of both SMS and pig manure.
Keywords: Spent mushroom substrate (SMS); Pig manure addition; Vermicomposting; Optimizing